Identifying Key Sites of Green Infrastructure to Support Ecological Restoration in the Urban Agglomeration - Hui Sun; Chunhui Liu; Jiaxing Wei (Land, 2021)
The loss and fragmentation of natural space has placed tremendous pressure on green infrastructure (GI), especially in urban agglomeration areas. It is of great importance to identify key sites of GI, which are used to economically and efficiently restore urban ecological network. However, in the existing research, few scholars have explored the identification and application of GI key sites. Taking the Southern Jiangsu Urban Agglomeration as an example, based on the ecosystem service assessment and landscape connectivity analysis, we identified the multi-class key sites of GI in the study area by MSPA, InVEST model, MCR model, and Linkage mapper. The results showed that: (1) a total of 60 GI sources and 130 GI corridors were extracted. The ecological resources of the study area were densely distributed in the north and south and sparsely in the middle. (2) Three-hundred eighty GI key sites were identified, including 53 water ecological points, 251 ecological fracture points, and 76 ecological pinch points. The GI key sites we identified were large in number and widely distributed, yet were hardly included in the existing ecological protection policies. These key sites should be prioritized in GI planning and differentiated for management strategies, ensuring that limited land resources and public funds can be directed to where restoration is really needed. The present study provides land managers and urban planners with additional tools to better understand how to effectively restore and develop the ecosystems of urban agglomerations in the context of scarce land resources.